Two 2D Zn(II) coordination polymers assembled from thiophene dicarboxylate and flexible N-(4-pyridylmethyl)imidazole derivatives: syntheses, crystal structures, and photoluminescent properties. (2nd January 2023) - Xue, Li-Ping; Wang, Qing
Abstract : Two 2D Zn(II) coordination polymers, formulated as [Zn( μ 2 -tdc)( μ -pmid)] (1 ), [Zn( μ 2 -tdc)( μ -pmmid)2 ·4H2 O]n (2 ) (H2 tdc = 2, 5-thiophenedicarboxylic acid, pmid = 1-(4-pyridylmethyl)imidazole; pmmid = 1-(4-pyridylmethyl)-2-methylimidazole) have been synthesized by reactions of Zn(OAc)2 ·2H2 O and H2 tdc with flexibleN-(4-pyridylmethyl)imidazole derivatives under the mild reaction conditions and characterized by single-crystal X-ray diffraction and other physicochemical methods. Structure determination demonstrates compound 1 displays a 2-fold 2D → 2D parallel interpenetrating structure, while compound 2 shows a 2D non-interpenetrating network. These results reveal that the substitute group in such N-(4-pyridylmethyl)imidazole derivatives might be the main factor resulting in these interpenetrating/ non-interpenetrating structures.Furthermore, compounds 1 and 2 show different thermal stabilities and strong solid-state luminescence emissions. GRAPHICAL ABSTRACT: UF0001